A 60-year dysfunctional relationship: How and why curriculum and assessment in fine art in England have always been problematic and still are. Issue 2 (1st October 2019) - Houghton, Nicholas
This article gives a brief account of the last 60 years of fine art in English art schools, concentrating on the curriculum and assessment only. Sixty years ago, there were national examinations and teachers taught to the test. The main causes of changes to assessment and curriculum were policy decisions of the 1960s, which abolished national examinations. This was followed a decade later by the need to accommodate post-Duchampian art practice. This new paradigm of fine art placed an emphasis on criticality, information and interdisciplinary practice with a reduced role for self-expression, formalism and traditional skills. The challenge this offered to the curriculum was that there was no longer any core set of skills or knowledge that all students need to learn. This has come up against higher education sector requirements to provide a detailed description of what all students should learn and against which they are assessed. Behind this intractable contradiction lies a clash of two incompatible world-views: the one interpretive within fine art and the other positivist held by those who determine assessment policy. A consequence of the ubiquitous adoption of these assessment regimes and the pressures of marketization is that teaching to the test is once again becoming the norm, albeit without standardized examinations.